2019
DOI: 10.1039/c9nj03698a
|View full text |Cite
|
Sign up to set email alerts
|

A Cu-Doped ZIF-8 metal organic framework as a heterogeneous solid catalyst for aerobic oxidation of benzylic hydrocarbons

Abstract: Cu(ii) ions doped into ZIF-8 MOFs are shown to activate C–H bonds in benzylic hydrocarbons to their corresponding alcohol/ketone products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…Further, Cu@ZIF-8 was characterized by powder XRD, FT-IR, UV-Visible DRS, SEM methods and the observed results are in line with the reported results. [49,50] Briefly, powder XRD patterns of ZIF-8, Cu@ZIF-8 and CU/ZIF-8 are shown in Figure 1 and they indicate that the structural integrity and crystallinity of ZIF-8 are not altered upon doping/adsorbing with Cu 2 + ions. The facile doping of Cu 2 + ions without affecting crystallinity of ZIF-8 is mainly due to the closer ionic radii between Cu 2 + (0.71 Å) and Zn 2 + (0.74 Å) ions.…”
Section: Resultsmentioning
confidence: 98%
“…Further, Cu@ZIF-8 was characterized by powder XRD, FT-IR, UV-Visible DRS, SEM methods and the observed results are in line with the reported results. [49,50] Briefly, powder XRD patterns of ZIF-8, Cu@ZIF-8 and CU/ZIF-8 are shown in Figure 1 and they indicate that the structural integrity and crystallinity of ZIF-8 are not altered upon doping/adsorbing with Cu 2 + ions. The facile doping of Cu 2 + ions without affecting crystallinity of ZIF-8 is mainly due to the closer ionic radii between Cu 2 + (0.71 Å) and Zn 2 + (0.74 Å) ions.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, it can be suggested that the incorporation of cobalt does not alter the topology of the framework structure and the original topology was retained due to: (i) the similarity of the ionic size of cobalt and zinc (Co 2+ 0.79 Å and Zn 2+ 0.74 Å) and (ii) the similarity of coordination number for the Co(II) and Zn(II) ions in this framework structure. 22 Fig. 1(D) presents the N 2 -adsorption isotherms of BE-S and AF-S and the accordingly determined BET surface areas are 1210 and 255 m 2 g À1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto, most previous reviews mainly summarized the properties of MOF materials, synthesis strategies, and applications. There are also some applications of MOFs as catalysts, but most of them focus on electrocatalysis, photocatalysis, and some oxidation reactions in liquid or gas phase reactions. However, as far as we know, the application of MOFs as catalysts in hydrogenation reactions has not been systematically summarized.…”
Section: Introductionmentioning
confidence: 99%